Structural analysis of novel trehalose-based oligosaccharides from extremely stress-tolerant ascospores of Neosartorya fischeri (Aspergillus fischeri). (26th June 2015) - Wyatt, Timon T.; Gerwig, Gerrit J.; Kamerling, Johannis P.; Wösten, Han A.B.; Dijksterhuis, Jan
Abstract: Different fungi, including the genera Neosartorya, Byssochlamys and Talaromyces, produce (asco)spores that survive pasteurization treatments and are regarded as the most stress-resistant eukaryotic cells. Here, the NMR analysis of a series of trehalose-based oligosaccharides, being compatible solutes that are accumulated to high levels in ascospores of the fungus Neosartorya fischeri, is presented. These oligosaccharides consist of an α, α-trehalose backbone, extended with one [α-d -Glc p -(1→6)-α-d -Glc p -(1↔1)-α-d -Glc p ; isobemisiose], two [α-d -Glc p -(1→6)-α-d -Glc p -(1→6)-α-d -Glc p -(1↔1)-α-d -Glc p ] or three [α-d -Glc p -(1→6)-α-d -Glc p -(1→6)-α-d -Glc p -(1→6)-α-d -Glc p -(1↔1)-α-d -Glc p ] glucose units. The tetra- and pentasaccharide, dubbed neosartose and fischerose, respectively, have not been reported before to occur in nature. Graphical abstract: Highlights: Stress-resistant ascospores accumulate mixtures of novel compatible solutes. These oligosaccharides contain an α, α-trehalose backbone. One, two or three glucose units are present at one side of the trehalose core. Two trehalose-based oligosaccharides are never reported in nature before.